Industrialization and environmental crisis: A representation of the nuclear disaster in Chernobyl prayer by Svetlana Aleksievéitch - Lopes, Alfredo Ricardo Silva; Rodrigues, Rauer Ribeiro [UNESP] (Universidade do Estado de Santa Catarina, 2019)
The article uses Svetlana Aleksievich's Voices of Chernobyl as representative to analyze the way humans have beaconed their energy production processes. Thus, literature emerges as a historical source to assess the relationship between the current Environmental Crisis and the industrial model that took shape from the mid-eighteenth century in England, one of the inaugural milestones of the Contemporary Era. Thus, it seeks to consider the production of the nuclear disaster as a representative event of the contemporary environmental crisis.
Industrialização e crise ambiental: A representação do desastre nuclear em Vozes de Tchernóbil, de Svetlana Aleksiévitch
Keywords: Contemporary history; Environmental crisis; Literature; Nuclear disaster of Chernobyl; Svetlana Aleksiévitch